Serum human chorionic gonadotropin levels on the day before oocyte retrieval do not correlate with oocyte maturity - Levy, Gary (2013)
OBJECTIVE: To evaluate the correlation of preretrieval quantitative serum hCG level with oocyte maturity. DESIGN: Retrospective cohort study. SETTING: Military assisted reproductive technology (ART) program. PATIENT(S): Fresh autologous ART cycles. INTERVENTION(S): Serum hCG level the day before oocyte retrieval. MAIN OUTCOME MEASURE(S): Linear regression was used to correlate serum hCG levels and oocyte maturity rates. Normal oocyte maturity was defined as ≥ 75% and the Wilcoxon rank sum test was used to compare serum hCG levels in patients with normal and low oocyte maturity. Threshold analysis was performed to determine hCG levels that could predict oocyte maturity. RESULT(S): A total of 468 ART cycles were analyzed. Serum hCG level was not correlated with hCG dose; however, it was negatively correlated with body mass index (BMI). Serum hCG levels did not differ between patients with oocyte maturity of <75% and ≥ 75%. Serum hCG levels did not correlate with oocyte maturity rates. Receiver operator characteristic and less than efficiency curves failed to demonstrate thresholds at which hCG could predict oocyte maturity. CONCLUSION(S): Serum hCG levels were not correlated with oocyte maturity. Although a positive hCG was reassuring that mature oocytes would be retrieved for most patients, the specific value was not helpful.